2018
DOI: 10.14744/anatoljcardiol.2018.81568
|View full text |Cite
|
Sign up to set email alerts
|

Higher diuretic dose within the first 72 hours is predictive of longer length of stay in patients with acute heart failure

Abstract: Objective:High-dose diuretic strategies during the first 72 h of hospitalization have been shown to improve symptom resolution in patients with acute heart failure with decreased ejection fraction; however, they have not been shown to decrease length of stay (LOS). This study aimed to examine a possible relationship between higher diuretic dosing in the first 72 h of hospitalization and longer LOS in such patients.Methods:In this retrospective study, we included 333 consecutive patients hospitalized for acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…I have read the article by Kato et al (1) entitled “Higher diuretic dosing within the first 72 h is predictive of longer length of stay in patients with acute heart failure” which was published in Anatol J Cardiol 2018; 20: 110-6, with great interest. In their study, authors reported that higher diuretic dosing in the first 72 h of hospitalization was an independent predictor of longer length of hospital stay in patients with acute heart failure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…I have read the article by Kato et al (1) entitled “Higher diuretic dosing within the first 72 h is predictive of longer length of stay in patients with acute heart failure” which was published in Anatol J Cardiol 2018; 20: 110-6, with great interest. In their study, authors reported that higher diuretic dosing in the first 72 h of hospitalization was an independent predictor of longer length of hospital stay in patients with acute heart failure.…”
mentioning
confidence: 99%
“…In addition, they concluded that there could be important predictors of the length of hospital stay that were not included in their study. Beside this, they reported that laboratory data of patients, including serum sodium level and cardiac troponin values, were recorded on admission and during the first 72 h of hospitalization (1). I would like to emphasize some important points about this well-written study.…”
mentioning
confidence: 99%
“…In previous issues of the journal, we read with great interest the article by Kato et al (1) entitled “Higher diuretic dosing within the first 72 h is predictive of longer length of stay in patients with acute heart failure” published in Anatol J Cardiol 2018; 20: 110-6. The study included 333 patients with acute heart failure, and the authors demonstrated that higher diuretic dosing in the first 72 h of hospitalization was an independent predictor for a longer length of stay.…”
mentioning
confidence: 99%